Consumer preferences for aquaponic produce: Implications from an experimental auction. Issue 4 (14th April 2018) - Short, Gianna; Yue, Chengyan; Abbey, Marie; Anderson, Neil; Phelps, Nicholas; Venturelli, Paul; Vickers, Zata
Abstract: Aquaponics is the integration of aquaculture and hydroponics to grow fish and plants together in one system. Many producers in the northern United States are attracted to aquaponics for its potential to produce indoors year‐round. However, little is known about consumer preferences for products grown in aquaponic systems. To address this knowledge gap, we conducted an experimental auction to measure the impact of information about production method on consumers' willingness‐to‐pay (WTP) for lettuce. For most participants, WTP was similar for both aquaponic and soil grown lettuce with overall average bids of $1.47 per 8 ounces and $1.48 per 8 ounces, respectively. Learning how samples were grown (either aquaponic or soil‐grown) rarely changed bids significantly, although on average, participants with environmental group membership lowered their bids for aquaponic lettuce samples. In general, higher frequency shoppers expressed higher average WTP for all types of lettuce. [Q100 Agriculture: General, Q220 Renewable Resources and Conservation: Fishery; Aquaculture]